Estimating flow rate in gauged and ungauged stations in Kuantan river basin using Clark method in Hec-HMS - Nadiatul Adilah, Ahmad Abdul Ghani; Nuramirah, Sharif (IOP Publishing, 2019)
Hydrologic simulation that engages incomputer models is the cutting edge to boost the understanding and provide further reliable outcomes in estimating flow rate. US Army Corps of Engineers has taken an initiative to develop a stable and dependent model, HEC-HMS that can be used for many hydrological simulations. The value of parameter needed for the simulation basically depends on the method chosen for loss, transform and base flow. In this study, the model parameters are changed and the model calibration had been performed separately for the three selected methods, the Soil Conservation Service Curve Number (SCS CN) loss method, the Constant Monthly base flow and the Clark Unit Hydrograph for transform method, to determine the most suitable simulation and to obtain the highest peak discharge for every sub-basin of the Kuantan River. Every flow simulated undergoes the validation and calibration process, with the Nash-Sutcliffe index used as a criterion to compare the outcomes between observed and simulated hydrographs. At the end of the study, it can be concluded that SCS Curve Number, Constant Monthly and Clark Unit Hydrograph is the best method for loss, base flow and transform method consecutively in estimating the flow rate in Kuantan River Basin.